MAPPING RESEARCH ON QUALITY OF LIFE IN INTELLECTUAL DISABILITIES: A BIBLIOMETRIC ANALYSIS - Dikmen, Mualla (İstanbul Aydın Üniversitesi, 2025)
This study explores the global research landscape on quality of life in individuals with intellectual disability between 2000 and 2025. Drawing on 527 documents retrieved from Web of Science and Scopus databases, the analysis employs bibliometric techniques such as performance metrics and science mapping using VOSviewer and Biblioshiny. The findings show an annual publication decrease rate of 3.6%, suggesting stagnation and uneven development in the field. Robert L. Schalock and Miguel Verdugo emerged as the most prolific and cited authors, with significant influence in the discourse surrounding quality of life. Thematic analysis based on keyword co-occurrence highlights “quality of life,” “autism,” and “family” as core research foci. Co-authorship patterns indicate moderate international collaboration, with the United States, United Kingdom, and Spain serving as prominent contributors in terms of both productivity and citations. Despite its multidisciplinary nature, the literature appears fragmented, with limited integration across disciplines and regions. The dominance of high-income countries and the scarcity of cross-national collaboration underscore the need for more inclusive and globally representative research efforts. Overall, this study offers a comprehensive overview of the intellectual development, influential contributors, and thematic directions in the field, while identifying gaps that can guide future research on the quality of life in intellectual disability.

Bu çalışma, 2000-2025 yılları arasında zihinsel engelli bireylerde yaşam kalitesi üzerine küresel araştırma manzarasını araştırmaktadır. Web of Science ve Scopus veritabanlarından alınan 527 belgeye dayanarak, analiz VOSviewer ve Biblioshiny kullanarak performans ölçümleri ve bilim haritalaması gibi bibliyometrik teknikleri kullanmaktadır. Bulgular, alanda durgunluk ve eşitsiz gelişme olduğunu gösteren %3,6'lık yıllık yayın azalma oranını göstermektedir. Robert L. Schalock ve Miguel Verdugo, yaşam kalitesi etrafındaki söylemde önemli etkiye sahip en üretken ve atıf alan yazarlar olarak ortaya çıkmıştır. Anahtar sözcüklerin birlikte bulunmasına dayalı tematik analiz, temel araştırma odakları olarak "yaşam kalitesi", "otizm" ve "aile"yi vurgulamaktadır. Ortak yazarlık kalıpları, orta düzeyde uluslararası işbirliğini göstermektedir; Amerika Birleşik Devletleri, Birleşik Krallık ve İspanya, hem üretkenlik hem de atıflar açısından önemli katkıda bulunanlar olarak hizmet vermektedir. Disiplinler arası yapısına rağmen, literatür parçalanmış görünmektedir ve disiplinler ve bölgeler arasında sınırlı entegrasyon vardır. Yüksek gelirli ülkelerin hakimiyeti ve uluslar arası iş birliğinin kıtlığı, daha kapsayıcı ve küresel olarak temsili araştırma çabalarına olan ihtiyacı vurgulamaktadır. Genel olarak, bu çalışma, alandaki entelektüel gelişim, etkili katkıda bulunanlar ve tematik yönler hakkında kapsamlı bir genel bakış sunarken, zihinsel engellilikte yaşam kalitesi üzerine gelecekteki araştırmalara rehberlik edebilecek boşlukları belirlemektedir.
MAPPING RESEARCH ON QUALITY OF LIFE IN INTELLECTUAL DISABILITIES: A BIBLIOMETRIC ANALYSIS
Keywords: Multicultural; Intercultural and Cross-Cultural Studies; Çok Kültürlü ve Kültürlerarası Çalışmalar